Preliminary observations about the influence of the upstream homogenization pressure on the colloidal stability of UHT milk in the ethanol test (Research, Society and Development, 2021)
The purpose of this work was to study the influence of the upstream homogenization pressure (before heat treatment) on the stability of pasteurized whole milk when submitted to the alcohol test, aiming at UHT processing without the addition of stabilizers. Four different homogenization pressures (0 MPa, 20 MPa, 40 MPa and 80 MPa, in addition to the control treatment) were evaluated at a temperature of 80°C (average homogenization temperature used in the UHT milk industry). Two methods of observation of the colloidal behavior of milk after the alcohol test (ethanol concentrations between 72% (v/v) and 96% (v/v), at 2% (v/v) intervals) were applied: direct visualization and particle size distribution (LS) analysis. The LS results showed that the 0 MPa treatment did not present significant difference (p>0.05) for values of d10 up to 86% alcohol (v/v), thus showing a higher stability when compared to the control treatment (with stability up to 82% (v/v) alcohol). It was found that the stability of the control, 20 MPa and 40 MPa treatments were maintained up to 80% alcohol (v/v) (p>0.05); a distinct behavior was observed in the 80 MPa treatment which presented a statistically significant difference (p